Phylogenetic and Molecular Evolutionary Analysis of Mitophagy Receptors under Hypoxic Conditions - Wu, Xiaomei; Wu, Fei-Hua; Wu, Qianrong; Zhang, Shu; Chen, Suping; Sima, Matthew (Frontiers in Physiology, 2017)
Abstract As animals evolved to use oxygen as the main strategy to produce ATP through the process of mitochondrial oxidative phosphorylation, the ability to adapt to fluctuating oxygen concentrations is a crucial component of evolutionary pressure. Three mitophagy receptors, FUNDC1, BNIP3 and NIX, induce the removal of dysfunctional mitochondria (mitophagy) under prolonged hypoxic conditions in mammalian cells, to maintain oxygen homeostasis and prevent cell death. However, the evolutionary origins and structure-function relationships of these receptors remain poorly understood. Here, we found that FUN14 domain-containing proteins are present in archaeal, bacterial and eukaryotic genomes, while the family of BNIP3 domain-containing proteins evolved from early animals. We investigated conservation patterns of the critical amino acid residues of the human mitophagy receptors. These residues are involved in receptor regulation, mainly through phosphorylation, and in interaction with LC3 on the phagophore. Whereas FUNDC1 may be able to bind to LC3 under the control of post-translational regulations during the early evolution of vertebrates, BINP3 and NIX had already gained the ability for LC3 binding in early invertebrates. Moreover, FUNDC1 and BNIP3 each lack a layer of phosphorylation regulation in fishes that is conserved in land vertebrates. Molecular evolutionary analysis revealed that BNIP3 and NIX, as the targets of oxygen sensing HIF-1α, showed higher rates of substitution in fishes than in mammals. Conversely, FUNDC1 and its regulator MARCH5 showed higher rates of substitution in mammals. Thus, we postulate that the structural traces of mitophagy receptors in land vertebrates and fishes may reflect the process of vertebrate transition from water onto land, during which the changes in atmospheric oxygen concentrations acted as a selection force in vertebrate evolution. In conclusion, our study, combined with previous experimental results, shows that hypoxia-induced mitophagy regulated by FUDNC1/MARCH5 might use a different mechanism from the HIF-1α-dependent mitophagy regulated by BNIP3/NIX.